(untitled) (Annals of Medical Research, 2021)
Aim: Maxillofacial (MF) traumas are most challenging group of patients in emergency departments (ED) due to occurrence of varying degrees of injury. The aim of this study was aid to ED clinicians in establishing correct diagnosis and to aid decision making process; to identify etiology of MF trauma presented to ED and to assess comorbid injuries. Materials and Methods: In this study, we retrospectively analyzed patients with MF trauma presented to ED between January, 2014 and July, 2017. The study included 73 patients among those with MF trauma admitted to ED. Data regarding age, gender, trauma mechanism, treatment modalities, presence of mandibular, zygomatic orbital base, zygomatic arch, frontal sinus and nasal sinus fracture were recorded and analysed.Results: Mean age was 36.18 years (min-max: 7-81 years). It was found that MF was significantly more prevalent in men than women. In our study, traffic accidents were observed to be the most common cause just like in developing countries.73 patients were surgically operated. 45 of the patients underwent open reduction and fixation with miniplates and screws. Conclusion: Maxillofacial trauma is common in our society. The most common causes are traffic accident and falls; followed by assault, head trauma and firearm injury.